Management of developing swimming performance in National Paralympic Committee of Indonesia - Nonik Rahmawati; Agus Kristiyanto; Muchsin Doewes (Kazimierz Wielki University, 2018)
The main objective of this study is to understand and analyze structural organization of NPC (National Paralympic Committee) of Indonesia on managing swimming performance,recruitment system, infrastructure management, funding management and implementation of the exercise management on managing swimming performance. This study was conducted at Head Office of NPC Indonesia and Kartasura Swimming Pool, Central Java Province. This studyis made in qualitative manner and presented in descriptive approach. The data collection is conducted by doing observation, document analysis, and interviews. The results of the management of developing swimming performance in NPC (National Paralympic Committee) of Indonesia are summarized as follows: 1) there are general chairman, the head of the achievement division, the head of the sports department, coach manager and then directed to the coach coordinator and coach's assistant in the organizational structure 2) recruitment of the organization is held by choosing people who concerned about NPC of Indonesia, recruitment of coach is held without any special tests, which is selected by: giving priority to athletes who have ever won medals and have experienced in coaching, while recruitment of athletes is held by using special test by NPC of Indonesia, 3) facilities, in the form of swimming's support tools, are given gradually by Ministry of Youth and Sports Affairsby submitting proposals. Meanwhile, facility such as swimming pool still depends on renting Kartasura Swimming Pool, 4) the funding is obtained from Ministry of Youth and Sports Affairs without any sponsorship, 5) training program is held by giving suitable program in general preparation, special preparation, pre match, and also considering athletes' physical condition, technique, and mental status. Training program can be developed according to the condition of each athlete. Based on the analysis, it can be concluded that management of developing swimming performance in NPC (National Paralympic Committee) of Indonesia have been going pretty well but some aspects need to be improved, such as: recruitment of organization and coaches haven't been done by any special test and the absence of private swimming pool for athletes.